Corporate Governance and Company Size in Reducing Tax Avoidance: Tata Kelola Korporasi dan Ukuran Perusahaan dalam Mengurangi Penghindaran Pajak - Nugroho , Dimas; Ernandi, Herman (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Tax avoidance has become a persistent issue in corporate financial management, influenced by company characteristics and governance practices. Specific Background: Previous studies have shown mixed findings regarding the relationship between firm size, profitability, leverage, and tax avoidance. Gap: Limited research has examined these variables simultaneously in the context of Indonesian listed companies. Aims: This study aims to analyze the relationship between company size, leverage, profitability, and corporate governance toward tax avoidance practices. Results: The findings indicate that corporate governance and company size significantly reduce tax avoidance, while leverage and profitability show mixed or insignificant effects. Novelty: This study provides empirical evidence of how governance quality moderates corporate tax behavior in emerging economies. Implications: The results suggest that improving governance mechanisms can enhance tax transparency and compliance in Indonesian firms. Highlights:• Corporate governance reduces tax avoidance through improved oversight.• Firm size correlates with higher tax compliance levels.• Leverage and profitability show mixed empirical outcomes. Keywords: Corporate Governance, Tax Avoidance, Firm Size, Profitability, Leverage